Foundations for sociorhetorical exploration : a rhetoric of religious antiquity reader - Robbins, Vernon K. (Vernon Kay), 1939-; Von Thaden, Robert H., Jr.; Bruehler, Bart B. (Bart Burdette) (Atlanta : SBL Press, 2016)
"As scholars develop innovative approaches to biblical interpretation, it is important to understand the foundations upon which these new approaches are built. This volume collects essays that represent intellectual milestones that are informing sociorhetorical interpretation during the twenty-first century. The essays are arranged into five parts: (1) Topos; (2) Cultural Geography and Critical Spatiality; (3) Rhetorolects and Conceptual Blending; (4) Rhetography; and (5) Rhetorical Force. Since biblical texts were written by embodied human beings who occupied distinctive spaces in specific time periods, it is important to have a set of tools that allows for a full-bodied interpretation. The essays in this volume help to show the importance of such a mode of reading and provide strategies to help interpreters perform their work in this manner"--
Part 5: Rhetorolects and RhetographyRhetography; Clothes Make the (Wo)Man; Contributors; Bibliography; Ancient Sources Index; Modern Authors Index; Subject Index
Includes bibliographical references and index.
Print version record and CIP data provided by publisher; resource not viewed.
Keywords: Bible. -- Socio-rhetorical criticism; BIBLES / General; RELIGION / Biblical Reference / General; RELIGION / Biblical Reference / Handbooks; Electronic books